Pretarsal structures in the family Parastrachiidae (Hemiptera: Heteroptera: Pentatomoidea) - Lis, Jerzy A. (Zootaxa, 2010)
Parastrachiidae, for a long time regarded as a subfamily within the Cydnidae (e.g., Schaefer et al. 1988; Schuh and Slater 1995; Gapud 1991), was raised to family level by Sweet and Schaefer (2002), and this position was then accepted by many heteropterists (e.g., Lis and Heyna 2001; Lis and Schaefer 2005; Hironaka et al. 2007; Schaefer and Kikuhara 2007; Lis 2010).